2019
DOI: 10.1186/s12913-019-4679-8
|View full text |Cite
|
Sign up to set email alerts
|

Are providers prepared for genomic medicine: interpretation of Direct-to-Consumer genetic testing (DTC-GT) results and genetic self-efficacy by medical professionals

Abstract: BackgroundPrecision medicine is set to deliver a rich new data set of genomic information. However, the number of certified specialists in the United States is small, with only 4244 genetic counselors and 1302 clinical geneticists. We conducted a national survey of 264 medical professionals to evaluate how they interpret genetic test results, determine their confidence and self-efficacy of interpreting genetic test results with patients, and capture their opinions and experiences with direct-to-consumer geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 41 publications
(47 reference statements)
2
25
0
Order By: Relevance
“…In contrast, in populations of primary care patients, studies have shown greater use of GPs to help understand and decide what to do with testing results, but again, with mixed findings [ 10 , 14 , 27 ]. On the physicians’ side, American GPs seem to be prepared to discuss DTCGT results with their patients to provide them with an accurate interpretation [ 2 , 19 , 33 ]. In any event, many authors agree on the need to discuss results with a professional as even though they may be easy to understand, they can often be misinterpreted [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in populations of primary care patients, studies have shown greater use of GPs to help understand and decide what to do with testing results, but again, with mixed findings [ 10 , 14 , 27 ]. On the physicians’ side, American GPs seem to be prepared to discuss DTCGT results with their patients to provide them with an accurate interpretation [ 2 , 19 , 33 ]. In any event, many authors agree on the need to discuss results with a professional as even though they may be easy to understand, they can often be misinterpreted [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that a PBS approach reduces anxiety and does not adversely impact a patient's psychological well‐being (Manchanda et al., 2019). While several studies show that non‐genetic providers have insufficient knowledge of cancer genetics and feel unprepared to counsel patients regarding genetic test results (Bellcross et al., 2011; Douma, Smets, & Allain, 2016), others report that non‐genetic providers may appropriately interpret results when specialists are not available (McGrath, Walton, Williams, Kim, & Bastola, 2019). Genetic counselors may seek to validate their perceptions of patient anxiety and non‐genetic provider knowledge at their institutions to determine optimal strategies to develop PBS protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The e-mail notice was successfully delivered to 358 HCPs (42 returned e-mails due to a full inbox or inactive e-mail address), of which 72 provided informed consent for the study for a response rate of 20%. This response rate is higher than previous studies that have investigated HCP experiences with DTC GT in practice, which have reported response rates between 2 and 15% [14-16]. The survey was open for a period of 8 weeks, with 3 reminder e-mails sent on a biweekly interval following the initial invitation.…”
Section: Methodsmentioning
confidence: 98%
“…Consequently, the knowledge and competence of HCPs with NGT are a growing priority [11-13]. While the experiences of HCPs with DTC genetic tests have been studied [14-16], research on the HCP clinical experience with NGT is at its infancy. Previous reports regarding NGT perceptions have reported a prominent knowledge gap among HCPs and students in training about how to incorporate NGT in practice and also a frequently reported desire for additional sources of nutrigenomics education [17-22].…”
Section: Introductionmentioning
confidence: 99%